Istikhdāmu al-Wasīlah at-Taʿlīmiyyah "Ludo" fī Tarqiyyati Mahārat al-Kitābah li-Ṭullāb al-Faṣl as-Sābiʿ fī al-Madrasah ath-Thānawiyyah "Mujāhidīn" Tumbang Sangai - M. Zainul Muttaqin; Muat (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2022)
Arabic is a compulsory subject that must be taught to Islamic schools, especially in MTs. Mujahidin Tumbang Sangai schools. In learning Arabic, the main thing that needs to be taught to students is their writing skills. The role of an active teacher and good mastery of materials is also a must. The reason is, students will be bored and saturated if the material provided by the teacher is not interesting. Then there needs to be learning methods and media such as games to facilitate students' understanding of Arabic lessons. The focus of this study is: 1). How is ludo learning media used in improving writing skills in grade VII MTs. Mujahideen Tumbang Sangai? 2). What are the advantages and disadvantages of using Ludo learning media in improving writing skills in grade VII MTs. Mujahideen Tumbang Sangai?             The objectives of this study are: 1). Knowing the application of ludo learning media in improving writing skills in grade VII MTs. Mujahidin Tumbang Sangai 2). Knowing the advantages and disadvantages of using Ludo learning media in improving writing skills in grade VII MTs. Mujahidin Tumbang Sangai             The research used from this scientific research is qualitative scientific research. Data collection techniques using observations, interviews, and documentation. Anilisis data used in this study using miles and Hubberman version that there are 4 stages that must be done, among others data collection ( data collection), data reduction (data reduction), data display (data appearance), data conclution drawing (conclusion). The validity of using source triangulation.             The results of the research can be: 1). the use of ludo learning media between lian easy to use, increase the creativity of teachers in delivering materials, fun in learning Arabic, and improve students' Arabic writing skills. 2). The advantages of using ludo learning media has a positive impact for students in learning Arabic, eliminating saturation, improving students' cognitive scores, motivating students to learn Arabic. The shortcoming is to cause noise due to the enthusiasm of students in playing ludo permianan so as to disturb other classes in learning, the lack of conduciveness of the class.